2007
DOI: 10.3177/jnsv.53.57
|View full text |Cite
|
Sign up to set email alerts
|

Oral Intake of Soy Isoflavone Aglycone Improves the Aged Skin of Adult Women

Abstract: Summary A double-blind, placebo-controlled trial was conducted to clinically evaluate the effect of soy isoflavone aglycone on the aged skin of middle-aged women. Twenty-six women volunteers in their late 30s and early 40s were randomly assigned to receive either a test food (13 women, the test food group) or a placebo food (13 women, the control group). These groups were given the test food (40 mg of soy isoflavone aglycone per day) and placebo, respectively, for 12 wk. The extent of linear and fine wrinkles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 28 publications
3
46
0
2
Order By: Relevance
“…Several dietary factors have been reported to improve skin elasticity by oral supplementation in women with, for example, a pine bark extract containing a variety of polyphenols, which had antioxidant effects (Marini et al, 2012); glucosyl-ceramide prepared from a beet extract (Hori et al, 2010); an oil formulation rich in fish oil (Segger et al, 2008); and soy isoflavone (Izumi et al, 2007). In some of those studies, enhanced production of extracellular matrix constituents was suggested as a possible mechanism for the improvement in skin elasticity, with the de novo synthesis of hyaluronic acid being induced by the pine bark extract (Marini et al, 2012) and fibronectin synthesis being upregulated by glucosyl-ceramide from the beet extract (Hori et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several dietary factors have been reported to improve skin elasticity by oral supplementation in women with, for example, a pine bark extract containing a variety of polyphenols, which had antioxidant effects (Marini et al, 2012); glucosyl-ceramide prepared from a beet extract (Hori et al, 2010); an oil formulation rich in fish oil (Segger et al, 2008); and soy isoflavone (Izumi et al, 2007). In some of those studies, enhanced production of extracellular matrix constituents was suggested as a possible mechanism for the improvement in skin elasticity, with the de novo synthesis of hyaluronic acid being induced by the pine bark extract (Marini et al, 2012) and fibronectin synthesis being upregulated by glucosyl-ceramide from the beet extract (Hori et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Skin hydration was measured by using a corneometer (CM 825, Courage & Khazaka Electronics) ( 10 , 11 ) . Malar skin elasticity was measured by an absorption method (Cutometer SEM575, Courage & Khazaka Electronics) ( 11 , 12 ) . In brief, a 2-mm region of skin was aspirated at 300 mbar for 2 s and then released.…”
Section: Methodsmentioning
confidence: 99%
“…Isoflavone is a heterocyclic phenol with a structure very similar to that of estrogens. Isoflavone displays like an estrogens and anti estrogen activity; influences sex hormone metabolism and their biological activity (Izumi et al, 2007;Lee et al, 2004), and prevents osteoporosis (Lee et al, 2004;Suh et al, 2003), arteriosclerosis (Mahesha et al, 2007), dementia (Lee et al, 2004), and cancer (Chan et al, 2003;Clubbs and Bomser, 2007).…”
Section: Introductionmentioning
confidence: 97%